Effects of different Familial Mediterranean Fever gene mutations and in vitro Colchicine treatment on Peripheral Blood Mononuclear Cells production of IL-6 - Daoud, AK; Rajab, WH; Alawneh, KM; Harfiel, MA Nizar (Bangladesh Journal of Medical Science, 2013)
Rationale: We wanted to study the effects of Familial Mediterranean Fever (FMF) genetic mutations in Northern Jordan population and in vitro Colchicine treatment on the peripheral blood mononuclear cells (PBMN) production of IL-6 as a marker of disease activity. Methods: - 17 FMF patients and 9 controls were studied. (4 patients had exon 10 mutations only (M680I and V726A), 5 patients had exon 2 mutations (R202Q and E148Q) only and 8 patients with both exon mutations (compound homozygous or heterozygous M694V and R202Q). PBMN cells were incubated with Lipopolysaccharide at 100ng/ml or colchicine 10 ng/ml alone or both. Results: The results showed higher IL-6 levels in the FMF group than control for all treatment modalities, (108.97 vs. 56.49 ng/ml for unstimulated cells) with the highest levels when both exons are involved. Exon 10 mutations were associated with a higher IL-6 level than exon 2 mutations only. Exon 2 mutations alone also were associated with a higher than control IL-6 levels suggesting that it is not a polymorphism phenomenon and is involved in the pathogenesis. In vitro Colchicine treatment caused an increase in the production of IL-6 - although not as high as with LPS - for all groups. Conclusions: Mutations occurring in exon 10 are more significant than mutations occurring in exon 2, although both are contributing to the disease. However colchicine was associated with a paradoxical increase in IL-6 levels. This observation needs confirmation with different colchicine levels in the culture medium and warrants thinking about its exact mechanism of action. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16659 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 370-377